ANALYSIS EFFICIENCY OF IRRIGATED RICE FARMING IN WONOSARI DISTRICT - Sepfrian, Bimoseno; Wahyu Utami, Indah; Filemon Waluyono, Garnet; Arsa Nugralistyo, Nafisan (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2023)
Farmers, as parties who have an important role in meeting people's food needs in agriculture, should have high selling prices and their welfare should be taken into account by the government. Agricultural development is a means of effort to improve the standard of living of farmers, increase income, expand employment and business opportunities, and expand markets both domestically and abroad. This can be achieved through advanced, efficient and resilient agriculture so that it can increase yields, improve quality and support regional development. This study aims to analyze income, efficiency and costs of irrigated lowland rice farming in Wonosari district, Klaten. The method used in this research is to determine the sample by means of purposive sampling. Data analysis uses farming analysis such as analysis of income, efficiency and costs. The results of this research are the average income earned on irrigated rice fields in Wonosari District Rp. 10,542,703.72/Ha. Farming costs obtained by irrigation rice farmers amounted to IDR 11,009,059.63/Ha. Revenue for irrigated lowland rice farming is IDR 21,551,763.35/Ha and the efficiency of irrigated lowland rice farming in Wonosari District is IDR 2.0.